TREATMENT OF MAN-WOMAN RELATIONSHIP IN PREETI SHENOY’S THE SECRET WISH LIST - Kashyap, Aparn; Richa (ShodhGyan-NU: Journal of Literature and Culture Studies, 2025)
This paper aims to study the treatment of man-woman relationships in Preeti Shenoy’s The Secret Wish List. The novel follows the journey of Diksha, a young woman trapped by traditional gender roles and societal expectations, who seeks to redefine her identity and pursue her dreams. At the outset, Diksha is confined to the conventional role of a wife and mother, where her aspirations are secondary to her familial duties. However, her relationship with her modern, independent friend Vibha acts as a catalyst for her emotional awakening. As Diksha confronts the emotional neglect in her marriage and realizes her unfulfilled desires, she begins her journey of self-discovery. This paper critically examines the evolution of Diksha’s man-woman relationship, focusing on how Shenoy challenges patriarchal norms and illustrates the shifting dynamics in contemporary relationships. In tracing the gradual change of Diksha (who was once a conventional wife) into an independent woman, the paper reveals the feministic principles of self-identity and assertion. The book displays both emotional and mental duress of gender disparity, and it champions female independence in relationships. By awakening Diksha, Shenoy tries to show the value of mutual respect, self gratification and self-individuality between a man and a woman in the contemporary society.